Evaluation of Peptide-Based Vaccines Against Group A Streptococcus in Staphylococcus aureus-Infected Mice - Ahmed O. Shalash; Haolan Sun; Yiru Cui; Jingwen Wang; Barb Arnts; Jannah Bauer; Waleed M. Hussein; Zeinab G. Khalil; Mariusz Skwarczynski; Istvan Toth (Vaccines, 2025)
Background: Group A Streptococcus (GAS) is a major human pathogen associated with serious diseases. Evaluating immune responses against GAS vaccines—immunogenicity, quality, and efficacy—is complicated by interference from co-infections, like Staphylococcus aureus (S. aureus). We aimed to evaluate peptide-based GAS vaccines in mice for antisera efficacy against standard and mutant GAS strains and to assess immunological methods under co-infection conditions. Methods: Female C57BL/6 mice were infected with S. aureus and immunized with various M-protein-derived peptide antigens: J8, J8i, J8i-J8i, and the native p145 sequence. Two novel, conserved M-protein-derived antigens (NTD and CTD2) were also evaluated. Enzyme-linked immunosorbent assays (ELISAs) were used to assess immunogenicity and GAS-specific antibody responses. Peptide antigens were either conjugated to or physically mixed with the PADRE T-helper epitope and tested for enhanced antisera immunogenicity and opsonic efficacy. Result: ELISA against the immunizing peptides as coating antigens reflected the immunogenicity, while p145-based ELISA correlated with GAS-specific antibody titres without S. aureus interference for J8-based vaccines. Immunogenicity ranked J8 > J8i ≈ J8i-J8i > p145. NTD and CTD2 antisera demonstrated opsonic activity, indicating protective potential. PADRE–J8 conjugates significantly enhanced antibody magnitude and quality, producing strong opsonic bactericidal responses against both standard and p145-mutant GAS strains. PADRE–J8i was effective only against standard strains. This is the first report to suggest at least two B-cell epitopes within the J8i peptide. Conclusion: These findings support the diagnostic utility of p145, NTD, and CTD2 under co-infection settings, and the vaccine potential of J8, NTD, and CTD2, particularly when conjugated to a T helper for enhanced antigen presentation.